2022
DOI: 10.1177/15589447221131851
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for 30-Day Complications and Unplanned Reoperation Following Surgical Treatment of Distal Radius Fractures

Abstract: Background: The purpose of this study was to identify demographic data, medical comorbidities, and perioperative factors that are associated with increased risk of overall surgical complications, wound complications, and reoperation within 30 days of open reduction and internal fixation (ORIF) of distal radius fractures. Methods: All adult patients undergoing ORIF of distal radius fractures in the National Surgical Quality Improvement Program database between 2005 and 2020 were identified. Patients were exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…ASA classification III-V was the greatest independent predictor of unplanned re-operation. Higher ASA classification is known to be associated with increased re-operation rates in prior studies in the orthopedic literature [ 21 , 22 ]. The ASA classification has been used since the 1940s to provide a categorization of operative risk; however, there are limitations including low inter-reporter reliability, vague criteria, and simplicity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…ASA classification III-V was the greatest independent predictor of unplanned re-operation. Higher ASA classification is known to be associated with increased re-operation rates in prior studies in the orthopedic literature [ 21 , 22 ]. The ASA classification has been used since the 1940s to provide a categorization of operative risk; however, there are limitations including low inter-reporter reliability, vague criteria, and simplicity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…43,49 Dialysis dependency has been associated with greater risk of in-hospital mortality, longer postoperative stay, and reoperations. 44,45 Chronic steroid use has been associated with increased risk for major, minor, and infectious complications in patients undergoing various orthopaedic procedures. 41,42 By controlling for smoking, dialysis, bleeding disorders, obesity, and steroid use in our binomial logistic regression, we have decreased the potential of confounding variables to affect the independent association between mFI-5 and 30-day complications in our patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified smoking, steroid use, bleeding disorders, dialysis, and obesity as the most pertinent risk factors for poor outcomes of fracture fixation procedures and bone healing. [40][41][42][43][44][45] Smoking has been associated with surgical site infections, postoperative wound complications, and reoperations after fracture fixation. [46][47][48] Bleeding disorders have been associated with increased risk of major postoperative complications and need for postoperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%